Patent Ductus Arteriosus Stenting via Percutaneous Common Carotid Artery Access for Ductus Dependent Pulmonary Blood Flow in Newborns and Infants: Experience in Latvia - Grīnberga, Zanda; Zaharāne, Elizabete; Sīlis, Pauls; Ozoliņš, Valts; Sikora, Normunds; Ligere, Elīna (Acta medica Lituanica, 2024)
Background: Newborn patients with cyanotic congenital heart diseases with ductus-dependent pulmonary blood flow require neonatal repair, or palliation with a secure source of pulmonary blood flow, up to definitive surgical correction or palliation of the malformation. There is growing experience of percutaneous patent ductus arteriosus stenting to maintain the ductal flow. Patients in need of PDA stenting are newborns or small infants and recent data suggests that a weight of <4 kg increases the risk of thrombosis from femoral arterial catheterisation. Carotid access for newborn cardiac catheterisation avoids femoral arterial injury and improves the catheter course for certain transvasal procedures. The aim of this study was to report the Riga Children’s Clinical University Hospital`s (CCUH) 7 year experience of patent ductus arteriosus stenting using the percutaneous transcarotidal approach in newborn babies and small infants with ductus-dependent critical heart diseases. Methods: A retrospective review of all newborn and small infants who underwent transcatheter arterial duct stenting through the percutaneous carotid artery approach at the CCUH in Riga, Latvia between the years 2013 and 2020. Results: In total, 8 patients underwent PDA stenting using the transcarotid approach between the years 2013 and 2020 in CCUH. The approach in all cases was chosen based on the anatomical features seen on echocardiography. In two cases, early restenting was necessary, while other patients had no procedure-associated complications. In the long term follow-up of 4 patients in two cases, dopplerography of the accessed common carotid artery showed stenotic changes up to 50%. Conclusions: PDA stenting using the transcarotid approach is currently considered a relatively safe method and does not have a greater risk of developing postprocedural complications compared to the transfemoral approach. Transcarotidal PDA stenting in neonates and small infants with ductus-dependent critical congenital heart disease is possible in small volume paediatric cardiac surgery centre to stabilise the patient prior to definitive surgery or palliation of complex CHD. The vascular access should be chosen depending on the anatomical features of the patient and the competency of the cardiac interventionalist. From our experience, long-term changes in the affected common carotid artery may develop in a substantial number of cases, they may not be clinically significant in midterm follow-up period but have to be reevaluated. However, further randomised studies are necessary with large cohorts and longer follow-up period.